Pengaruh Kemampuan Kerja dan Motivasi Terhadap Kinerja Pegawai Negeri Sipil di Dinas Infolahtal Mabesal Jakarta - Mursidi (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2020)
This study aims to examine and analyze the effect of work ability and motivation on the performance of civil servants in the Dinas Informasi dan Pengolahan Data Angkatan Laut, hereinafter abbreviated as PNS Disinfolahtal. Data collection was carried out through distributing questionnaires and carried out on 32 PNS Disinfolahtal. Data analysis in this study used SPSS version 21. The data testing technique used in this study included validity testing with factor analysis, reliability testing with Alpha Cronbach. Classic assumption test and multiple linear regression analysis, to test and prove the research hypothesis. The results of the analysis show that work ability has a positive effect on the performance of PNS Disinfolahtal and motivation has a positive effect on the performance of PNS Disinfolahtal.